A Learning Culture of Generation Z in Arabic and English Language Education in the Era of Digital Disruption - nurfadhila, ulfah; Aisyah Fajriantini; Renni Mayasari (Manajemen Pendidikan Program Doktor, 2025)
This study aims to describe the learning culture of Generation Z in Arabic and English language education in the era of digital disruption. This qualitative literature study employs a descriptive-analytical approach by examining relevant books and scientific publications from the last decade to identify the characteristics, learning behaviours, and technological influences shaping this generation. The research objects are studies discussing Generation Z and their learning culture in language education, while data were collected through documentation techniques and analysed using content analysis. The findings show that Generation Z demonstrates a fast, visual, interactive, and technology-based learning orientation, supported by digital platforms, multimedia resources, and gamified learning environments. Their learning culture reflects autonomy, collaboration, and global connectivity, yet it is also challenged by digital distraction, low critical digital literacy, and unequal digital resource availability—particularly in Arabic language learning. English learning benefits from abundant digital materials, while Arabic learning remains limited in academic digital content. The study concludes that effective language education for Generation Z requires blended learning, gamification, critical digital literacy reinforcement, and the active role of lecturers as facilitators who guide students to use technology productively. These results imply the need for curriculum redesign, pedagogical innovation, and improved digital infrastructure to support adaptive and future-oriented language learning.